Genetically confirmed chronic granulomatous disease in a Kenyan child: case report - Marangu-Boore, Diana; Kambuni, Fred; Onyinkwa, Mary; Ramprakash, Stalin; C.P., Raghuram; Eley, Brian; Bhattad, Sagar (Frontiers in Immunology, 2023)
Introduction We report the first case of genetically confirmed chronic granulomatous disease (CGD) in a Kenyan child. Clinical findings A 7-month-old male infant, the only child of non-consanguineous parents, presented with cough, fever, fast breathing, oral thrush, and axillary lymphadenopathy ipsilateral to the Calmette–Guérin bacillus scar. He had been hospitalized 5 weeks prior for severe pneumonia. Plain chest radiography showed bilateral patchy airspace opacification; chest computed tomography revealed multiple large lung nodules and left axillary lymphadenopathy. HIV ELISA was negative; tuberculin skin test was positive; lymph node biopsy macroscopically revealed caseous granulomas seen on histology; isoniazid- and rifampicin-susceptible Mycobacterium tuberculosis complex isolate was detected on the Hain test. First-line anti-tuberculous drugs were added to his empiric treatment comprising piperacillin–tazobactam, amikacin, cotrimoxazole, and fluconazole. He was discharged after 10 days based on clinical resolution. Diagnoses, interventions, and outcome An inborn error of immunity (IEI) was considered given the recurrent fevers and atypical lung nodules. Genetic analysis revealed a hemizygous pathogenic variant on CYBB in keeping with X-linked CGD. The child’s fevers recurred 2 weeks post-discharge but completely resolved on prophylactic itraconazole and cotrimoxazole. He underwent a successful haplo-identical hematopoietic stem cell transplantation at an experienced center in India with his father as the donor and is currently doing well on post-transplant follow-up. Conclusion Genetic testing is relatively accessible and cost-effective for the diagnosis of IEI in low-and-middle-income countries. Expert multi-disciplinary collaboration is key for successful outcomes.